ANALYSIS OF NETWORK PLANNING WITH THE CRITICAL PATH METHOD IN THE FRAMEWORK OF PROJECT TIME AND COST EFFICIENCY (Case Study of the Implementation of the Masnana Section Road Construction Project – Wali, Namrole District, South Buru Regency) - Marfien Hadi Waluyo; Jozef R. Pattiruhu; Stenly Ferdinandus (SEAN Institute, 2023)
CPM (Critical Path Method) is one of the time-oriented Network Planning Methods that leads to determining project scheduling and time estimates that are terministic/definite. The purpose of research with this method is to determine the time and cost of the project and find out what activities are included in the critical activities. The population in this study is the Masnana – Wali Section Road Development project in South Buru Regency, Namrole District which is handled by CV. Mighty Son. The sample used for the Masnana Section Road Construction project - Wali for the period October (17 October 2022) - December (08 December 2022). Data collection techniques in this study were interviews and observations. Data analysis techniques use the CPM (critical path method) method. Based on the results of the research and discussion, the form of the critical network for the Masnana - Wali Section Road Development project in South Buru Regency, Namrole District is ABCDEFGHMNNOPQRSTUVY with an efficient time duration of 123 days from the normal time of 124 days. This time duration is the most efficient time after being accelerated using the CPM method, the total cost of the Masnana - Wali Road Development project in South Buru Regency, Namrole District with an efficient time of Rp. 2,512,286,813 which of the initial cost of Rp. 2,497,872,247.68. This time duration is the most efficient time after being accelerated using the CPM method, the total cost of the Masnana - Wali Road Development project in South Buru Regency, Namrole District with an efficient time of Rp. 2,512,286,813 which of the initial cost of Rp. 2,497,872,247.68. This time duration is the most efficient time after being accelerated using the CPM method, the total cost of the Masnana - Wali Road Development project in South Buru Regency, Namrole District with an efficient time of Rp. 2,512,286,813 which of the initial cost of Rp. 2,497,872,247.68.The optimum duration and cost results obtained from this Crashing analysis can be considered for its application in project implementation. This is because the results of time and cost optimization show that a shorter implementation duration will require greater implementation costs compared to normal duration and cost conditions.